Today's police and sheriff recruits : insights from the newest members of America's law enforcement community - Castaneda, Laura Werber (Rand Corporation monograph series., 2010)
For much of the past decade, police and sheriff's departments faced considerable challenges in attracting and retaining recruits, such that many departments struggled to maintain their size. Although the economic downturn has altered this situation, police and sheriff's departments should expect that the tight labor market of the past decade will return. This volume summarizes a 2008-2009 survey fielded to recent police officer and sheriff's deputy recruits nationwide. The survey asked recruits why they chose a career in law enforcement, why they chose the particular agency that they joined, what they felt were the downsides of a career in law enforcement, and what could be done to improve their department's recruiting efforts. In discussing the survey results, the authors focus on how understanding modern recruits can help departments refine their recruitment practices and develop a workforce well suited to community-oriented policing.